2018
DOI: 10.1186/s12882-018-0993-3
|View full text |Cite
|
Sign up to set email alerts
|

Off-clamp partial nephrectomy has a positive impact on short- and long-term renal function: a systematic review and meta-analysis

Abstract: BackgroundOngoing efforts are focused on shortening ischemia intervals as much as possible during partial nephrectomy to preserve renal function. Off-clamp partial nephrectomy (off-PN) has been a common strategy for to avoid ischemia in small renal tumors. Although studies comparing the advantages between off-PN with conventional on-clamp partial nephrectomy (on-PN) have been reported, the impact on short- and especially long-term renal function of the two surgical methods has not been discussed seriously and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
1
18
0
3
Order By: Relevance
“…WIT is an important indicator of perioperative period [18]. Kidney is a highly oxygen-dependent organ, and the damage to kidney caused by WIT is mainly caused by ischemia reperfusion [19], which directly affects the postoperative renal function of patients.…”
Section: Discussionmentioning
confidence: 99%
“…WIT is an important indicator of perioperative period [18]. Kidney is a highly oxygen-dependent organ, and the damage to kidney caused by WIT is mainly caused by ischemia reperfusion [19], which directly affects the postoperative renal function of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Wen et al have reported less decrease in renal function in off-clamp surgery compared to that in onclamp surgery (weighted mean difference: 4.81 mL/min/1.73 m 2 ; 95% con dence interval: 3.53-6.08; p < 0.00001) [9]. Meanwhile, several studies have failed to show the advantages of off-clamp surgery in eGFR preservation over clamping surgery in pneumoperitoneum settings [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…As marked compensatory hypertrophy is a marker of parenchymal destruction of the operated kidney (contralateral hypertrophy of the order of 20% after radical nephrectomy), this minimal contralateral hypertrophy is an additional argument to confirm that embolization before partial nephrectomy is to be considered a nephron-sparing technique. Whether or not to perform renal arterial clamping during partial nephrectomy is still debated, one meta-analysis seemed to show a better preservation of renal function in the short and medium term with the "off-clamp" technique, but another meta-analysis with a longer follow-up period showed that at 5 years the difference in renal function was no longer significant between the on-clamp and off-clamp methods 23,24 . However, if a clamp appears necessary to control bleeding, its duration (< 25 min) and selectivity will lead to better functional results 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not to perform renal arterial clamping during partial nephrectomy is still debated, one meta-analysis seemed to show a better preservation of renal function in the short and medium term with the "off-clamp" technique, but another meta-analysis with a longer follow-up period showed that at 5 years the difference in renal function was no longer significant between the on-clamp and off-clamp methods 23 , 24 . However, if a clamp appears necessary to control bleeding, its duration (< 25 min) and selectivity will lead to better functional results 25 .…”
Section: Discussionmentioning
confidence: 99%